ZnO-NiO Composites for Photocatalysis of Methylene Blue - Poliukhova, Valeriia; Orlov, Anatolii; Cho, So-Hye (2018 IEEE 38TH INTERNATIONAL CONFERENCE ON ELECTRONICS AND NANOTECHNOLOGY (ELNANO), 2018)
Zinc Oxide nanoparticles were synthetized by a simple sol-gel method with pH modifier at a low temperature near 0 degrees C. The required experimental conditions to reach the size of nanoparticles under 50 nm are: dropwise addition of precursor solutions zinc acetate dihydrate and sodium hydroxide in absolute ethanol while stirring in ice bath and isopropanol washing. Obtained ZnO nanopowder was mixed with different nickel chloride amounts by impregnation method and then annealed at 300 degrees C in air. By adding 1% and 5% of nickel a combined system of structures was resulted: ZnO, ZnNixO alloys, and NixO all of which showed a better photocatalytic activity than as-synthetized material. When Ni was used in 10% quantity and the resulting materials showed no alloy phase but only composite structure, ZnO and NixO and exhibited the best photocatalytic activity. In this work the characteristics of all samples were studied by X-ray diffraction (XRD), which reveals the crystallite growth with the increase of the nickel concentration. By scanning electron microscopy (SEM) and transmission electron microscopy (TEM) the morphological properties were examined. Light absorption characteristics were measured in the wavelength range from 350 to 800 nm (UV-Vis spectroscopy). The photocatalytic activity of ZnO-NixO nanoparticles was defined by the degradation of Methylene Blue under the UV-light illumination.